Effect of Ionizers on Indoor Air Quality and Performance of Air Cleaning Systems - Francisco J. Romay; Qisheng Ou; David Y. H. Pui (Aerosol and Air Quality Research)
Abstract Corona ionizers are used to enhance the effectiveness of indoor air cleaners, remove odors, and to promote inactivation of viruses attached to airborne particles. However, there is limited experimental evidence of the effectiveness of ions in indoor air quality, and many commercial products have ambiguous or misleading performance statements. This study measured the effect of corona generated ions on particle wall deposition and on the performance of air cleaning systems. The experiments measured the indoor particle concentration decay of a polydisperse NaCl aerosol as a function of time for a variety of indoor room conditions including: (1) zero ventilation in the room, (2) HVAC system (100% outdoor air) at fixed flow rate, (3) Indoor air cleaners at different flow settings. For the zero-ventilation case, unipolar ions enhance wall particle deposition by a factor of 2, while bipolar ions do not enhance particle wall deposition. For the HVAC system and indoor air cleaners, the aerosol decay rates in the room increased by 10 to 30%, depending on the operating conditions. Ion and ozone concentrations were also measured in the room. This work demonstrates that unipolar ions can help improve indoor air quality, particularly in poorly ventilated environments, and have a measurable modest enhancement of the performance of air cleaning systems.